2021
DOI: 10.1111/1365-2656.13444
|View full text |Cite
|
Sign up to set email alerts
|

Interrelated impacts of climate and land‐use change on a widespread waterbird

Abstract: 1. Together climate and land-use change play a crucial role in determining species distribution and abundance, but measuring the simultaneous impacts of these processes on current and future population trajectories is challenging due to time lags, interactive effects and data limitations. Most approaches that relate multiple global change drivers to population changes have been based on occurrence or count data alone. 2. We leveraged three long-term (1995-2019) datasets to develop a coupled integrated populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 74 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…Our results suggest that a lack of environmental effects associated with parameters in IPMs should be simulated before researchers conclude that no relationship exists as there may be insufficient information to identify an ecological relationship. Despite these potential challenges, several recent studies have identified environmental relationships with vital rates using an IPM (e.g., Oppel et al, 2014; Saunders et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that a lack of environmental effects associated with parameters in IPMs should be simulated before researchers conclude that no relationship exists as there may be insufficient information to identify an ecological relationship. Despite these potential challenges, several recent studies have identified environmental relationships with vital rates using an IPM (e.g., Oppel et al, 2014; Saunders et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A feature of many of the reviewed studies was the use of chosen habitat quality proxy variable(s) as inputs into sophisticated ecological analyses, such as habitat suitability models (e.g., Guan et al, 2016;Hsu et al, 2014;Tang et al, 2016;Wen et al, 2016), carrying capacity estimates (e.g., Collazo et al, 2002;Mu et al, 2022;Stillman et al, 2000), population viability analyses (e.g., Mattsson et al, 2012;Saunders et al, 2021;Weegman et al, 2022), or to predict the outcome of management interventions on waterbird vital rates (e.g., Beerens et al, 2015;Toral et al, 2012). Where the predictor variables for these analytical approaches covered large spatial extents or could be sourced from extensive temporal archives, knowledge gained from site-level studies could be extrapolated in individually marked birds, limited spatial scale, and substantial costs (Buderman et al, 2020).…”
Section: Applicationsmentioning
confidence: 99%
“…Twenty‐three bird species showed a significant association with NAO − (Table 2), in studies from Canada, the USA, the UK, Norway, Sweden, Denmark, Romania, and Spain (Jonzen et al ., 2002; Almaraz & Amat, 2004; Olsen & Schmidt 2004; Grosbois & Thompson, 2005; Votier et al ., 2005; Weatherhead, 2005; Anders & Post, 2006; Zydelis et al ., 2006; Figuerola, 2007; Balbontin et al ., 2009; Goodenough, Elliot & Hart, 2009; Lewis et al ., 2009; Pearce‐Higgins et al ., 2009; Gaston & Robertson, 2010; Bustnes et al ., 2013; Jensen et al ., 2014; Veit & Manne, 2015; Guery et al ., 2017; Schimpf et al ., 2020; Baltag, Kovacs & Sfica, 2021; Saunders et al ., 2021; Table S1). They spanned diverse taxa from loons, cormorants, and eiders to New World blackbirds and Old World finches.…”
Section: Impact Of Naomentioning
confidence: 99%
“…Movements of organisms such as seasonal bird migrations create teleconnection (strong links) among distant regions, and these processes at the broad scale can interact with processes at local scales, resulting in non‐linear dynamics (Heffernan et al ., 2014). Migratory birds are highly susceptible to shifts of broad‐scale climate; there is evidence for changes to breeding [fecundity, clutch size, breeding probability, provision of food for offspring, fledging success, and nesting success (Ancona et al ., 2011; Tompkins & Anderson 2021)], food sources or prey abundance (Pardo et al ., 2013; Saunders et al ., 2021; Tompkins & Anderson 2021), survival [differential survival according to age, changes in migratory tactics and foraging costs (Dugger et al ., 2016; Guery et al ., 2017; Tjornlov et al ., 2020)], and phenology [hatching date and laying dates of birds, or plant and insect phenology (Lorentsen et al ., 2015; Gonzalez‐Braojos et al ., 2017; Morganti et al ., 2019)]. Thus, it is important to investigate how bottom‐up chain effects link broad‐scale and local‐scale climate effects, and to disentangle the independent effects of broad‐ and local‐scale climate.…”
Section: Perspectivesmentioning
confidence: 99%